Effect of Topical Cyclosporine A (0.05%) in Treatment of Corneal Subepithelial Infiltrates after Adenoviral Keratoconjunctivitis - Hussain, Md Emdad; Quader, Mohammad Abdul (Community Based Medical Journal, 2024)
A retrospective study was done in Bangladesh Naval Ship Patenga Hospital at Chattogram, Bangladesh, from July 2021 to December 2022, to evaluate the clinical benefit and effectiveness of 0.05% cyclosporine A (CsA) eye drop in the treatment of symptomatic corneal sub-epithelial infiltrates (SEIs) related with adenoviral keratoconjunctivitis that are resistant to tapering of corticosteroid eye drops. We reviewed 15 patients (20 eyes) who had symptomatic corneal SEIs after adenoviral keratoconjunctivitis that were resistant to tapering of corticosteroids eye drops and later, who were subsequently treated with cyclosporine A (0.05%) eye drops. Data was collected and recorded including best corrected visual acuity (BCVA), intra ocular pressure (IOP), evaluation of severity of corneal SEIs, i.e., corneal subepithelial infiltrate scoring (CSIS) prior to beginning of treatment and at the last follow-up visit. Ten males (66.6%) and Five females (33.3%), mean age of 34.2±15.4 years were included in this study. The patients average topical CsA 0.05% use duration was 4.5 months (3-6 months). The mean BCVA (logarithm of minimum angle of resolution) before and after the treatment were 0.17±0.16 and 0.06±0.06 respectively, CSIS 1.072±0.69 and 0.33±0.23 respectively, IOP 20.06±2.82 and 14.73±2.60 mm of Hg respectively. There were statistically significant improvements in BCVA (P=0.003), reduction of CSIS (p=0.002) and reduction of IOP (p=0.001) at the last follow-up visit. 17 eyes (85%) showed clinical improvement and 3 eyes (15%) showed decreased SEI which did not fully disappear within 3-6 months. The no of eyes which had clinical improvement with CSIS score 0 were decided to discontinue of CsA treatment in the last follow-up visit. Patients reported a reduction in the severity of symptoms after the treatment. The patients reported foreign body sensation, glare or other side effects with topical CsA treatment, but overall patients noted improvement of vision and satisfaction with topical CsA treatment. Topical CsA (0.05%) is a safe and effective corticosteroid sparing alternative drug for the treatment of corneal SEIs after adenoviral keratoconjunctivitis, especially in patients who did not respond to other treatment modalities and have undesired side effects from using long term topical steroid. CBMJ 2024 January: vol. 13 no. 01 P: 35-40